EDUKASI DAN PENANGULANGAN DAMPAK BULLYING DENGAN PEMBELAJARAN EMPATI DAN STORYTELING - Vella Anggresta; Siska Maya (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Bullying is an intentional and deliberate hostile act aimed at hurting, such as frightening through the threat of aggression and causing terror. This behavior can take many forms, from verbal abuse, physical violence, extortion, intimidation, and discrimination. Bullying perpetrators bullying because they have a low empathy ability and do not want to tell others. Community service activities aim to provide education about bullying, its impact, and how to overcome it with empathy learning and storytelling methods so that there are no more losses experienced by students at school because of unfavorable treatment from their peers. The technique used in the implementation is observation, interview, and counseling about bullying. Most of the students of the Indonesia-Akhwat Quran School in Mega Mendung, Bogor Regency, have experienced or even bullied their friends, but they did not know that this was wrong. With this counseling, they began to find out the harmful effects of bullying and the desire to improve themselves.